APPLICATION OF THE METHOD OF PEER TUTORS LEARNING TOWARDS THE LEARNING RESULTS OF STUDENTS ON THE MATERIAL ANALYZED ROD STYLES ON CONSTRUCTION ORDER IS SIMPLE IN CONSTRUCTION AND PROPERTY BUSINESS GRADE SMK NEGERI 1 PALANGKA RAYA 2017/2018 - Ester Dwi Sartika Simanjuntak; Yulin Patrisia (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2019)
The study was backed by the student learning outcomes by building construction that is still relatively low, namely under the value minimum mastery of 70.00. Learning activities conducted where a teacher is one of the determinant of the success of the learning process of students. In practice, the real educators often use only lectures and occasional FAQs then gave the matter of exercise to be undertaken. This less learning environment tends to make students passive and less involved in the learning process. Many students against the methods used by teachers that will affect on learning outcomes of students and learning on how to think actively. This study uses one of the methods of learning which involves the entire students to be active in learning activities so it is expected it can improve student learning outcomes with Peer Tutors Method. The purpose of this research is to know the results of student learning after the application of the learning method of Peer Tutors. This research is a descriptive research with quantitative approach. Samples taken with purposive sampling technique so students of Class X BKP SMK Negeri 1 Palangka Raya Academic Year 2017/2018 which amounted to 22 students designated as samples. Data collection techniques used in this research is in the form of a written test instruments namely multiple choice tests consisting of pretest (initial test) and post test (final test). Validation of the grain problem initial tests and final tests done by three raters consisting of two professors of Civil Engineering Education, University of Palangka Raya and one teacher who teach Mechanics Engineering at SMK Negeri 1 Palangka Raya. Engineering analysis on research using quantitative data in the form of numbers or score obtained from test results of student learning. The results of the research showed an increase from the pretest before the application of the method only 23%, or 5 of the 22 students who meet the minimum criteria of completeness (KKM). Whereas after Peer Tutor learning method was applied, the results of postest showed a 100% or all students met the criteria minimum completeness (KKM) and results of student learning increased by 77%.